Mowa Ślązaków – gwara, dialekt czy język regionalny (w związku z próbą zmiany statusu prawnego) - Jadwiga Wronicz (Ksiegarnia Akademicka Publishing, 2021)
The speech of the Silesians: subdialect, dialect or a regional language (with reference to the attempted change of the legal status)